Synthesis of a Photocurable Ladder-like Poly(phenyl-co-mercaptopropyl)silsesquioxane as Gate Dielectric Material - Lee, Albert S.; Baek, Kyung-Youl; Hwang, Seung Sang (TAYLOR & FRANCIS LTD, 2013)
A new photocurable ladder-like poly(phenyl-co-mercaptopropyl)silsesquioxane (LPPMPSQ) was synthesized in one pot via base catalyzed hydrolysis-polycondensation of a comonomer mixture of phenyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane. Obtained LPPMPSQ was characterized by H-1 NMR, FT-IR, Si-29 NMR, TGA, and the electrical (k = 3.6) and mechanical properties (surface modulus = 4.9 GPa) found to be suitable for application as a photocurable gate dielectric material.